Sacrifice, discounting and climate policy : five questions - Larry S. Karp (Center for Economic Studies and ifo Institute (CESifo), 2009)
I offer a selective review of discounting and climate policy. Analytic and numerical models show that different assumptions greatly change the degree to which decisions about climate policy depend on the discount rate. I discuss a claim that standard models exaggerate the current generation's sacrifices needed to internalize climate damages. This claim, if correct, affects the role of discounting. I argue that the assertion that the risk of catastrophic damage overwhelms discounting is unfounded. I show that the claim that we view the world in perspective implies hyperbolic rather than constant discounting. climate change ; discounting ; intergenerational conflict ; catastrophic risk ; hyperbolic discounting
Keywords: C61; C73; D63; D99; Q54; 330; Klimaschutz; Klimaveränderung; Soziale Diskontrate; Generationenbeziehungen; Naturkatastrophe